Business opportunities and challenges as the two sides of the climate change: Corporate responses and potential implications for big data management towards a low carbon society - Roman Pais Seles, Bruno Michel [UNESP]; Lopes de Sousa Jabbour, Ana Beatriz; Jabbour, Charbel José Chiappetta; de Camargo Fiorini, Paula [UNESP]; Mohd-Yusoff, Yusliza; Tavares Thomé, Antônio Márcio (Elsevier, 2018)
Climate change represents a long-term risk to society, and this risk extends to organizations across several sectors. The risks associated with climate change have both pros and cons, and it is thus important to understand how organizations deal with the opportunities and challenges that climate change presents. Furthermore, big data has gained increasing prominence due to its potential to transform ways of doing business. It is therefore important to understand the implications which big data will have for managing corporate responses to the opportunities and challenges presented by climate change. In this context, this article aimed to identify and analyze the challenges and opportunities that the climate crisis presents for organizations and to understand how organizations respond to this scenario, while examining the implications of big data management. This work adopted a structured literature review research method. The review showed that the opportunities emerging from the climate crisis tend to improve performance (environmental, financial and operational) as well as generating new business, while the challenges are related to the lack, or inefficiency, of governmental and regulatory support and an increase in costs. It was also identified that organizations respond to the climate crisis by investing in research and development, as well as through cooperation with other organizations. The results of this research serve as a guide for organizations that are concerned with the climate crisis situation, but currently can neither face the challenges it presents nor realize that this apparently threatening scenario also holds great business potential. The article also contributes to the debate on climate change policy by means of shedding light on possible methods to encourage organizations to make short-term investments to deal with the contingencies presented by climate change. Finally, the article also highlights the effects of big data.
Keywords: Big data; Climate change; Environmental management; Global warming; Sustainable operations